Automatic Dam Shutter for Fish Breeding Pond using Arduino: Automatic Dam Shutter - Nadzri, Muhamad Muzamil; Hashim, Hairulazwan (Progress in Engineering Application and Technology, 2021)
This idea is about to improve the poor allocation of water, inefficient use, lack of adequate and integrated management of the water. Arduino is used to controlling the process of opening and closing the gate. This project aims to supply water from the dam to the fish breeding pong during the drought season. The automation of the dam is used by Arduino to control the different parameters such as level and flow with the real-time implementation of gate control.